The relationship of decision-making style and reaction agility performance regarding the type of stimulus in handball - Horička, Pavol; Šimonek, Jaromír; Paška, Ľubomír; Popowczak, Marek (Studia sportiva, 2024)
The purpose of this study was to verify the influence of contextual perception in sports on performance in reaction agility to a specific and non-specific stimulus on a sample of handball players. The object of the research was eleven players of the junior handball team playing in the top league (age: 16.73 years; decimal age 16.46 years). Visual signaling and video projection. and a modified Y-test of reaction agility were used. In this study. two goals were set: a) to compare the performance level in the Y agility test with respect to a simple non-specific and a complex specific visual stimulus in the form of filmed scenes of the opponent's attacking actions. which simulated real situations in performance handball; b) find out the possible relationship between performance in the agility test and reaction time. decision-making competence. anxiety and overload and involvement in decision-making and performance with regard to the nature of the stimulus. A questionnaire (CETD) was implemented in the sample to assess the decision-making style of athletes in a specific area.